The Role of Parental Social Support on Adolescent Boys' Emotional Intelligence - Refitha Rachmadanisya; Nandy Agustin Syakarofath (Universitas Negeri Semarang, 2025)
Emotional intelligence has an important role. High emotional intelligence can help in overcoming stress, reducing anxiety and depression, and increasing adolescents' motivation to achieve goals. One of the factors that can affect the level of emotional intelligence is external factors, one of which is parents. This study investigated parental social support's role in adolescent boys' emotional intelligence. This study uses a quantitative method. The sample of this study was taken using accidental sampling and purposive sampling techniques, involving 126 adolescent boys aged 14 – 18 years. Then, the researchers used the Parental Social Support scale and the Wong & Law Emotional Intelligence Scale (WLEIS). Furthermore, a simple linear regression analysis technique was chosen to test the hypothesis in this study. The findings of this study show that parental social support has a positive role that contributes 4.4% (R2 = 0.044) to the variation in emotional intelligence. The higher the parental social support that adolescent boys have, the higher the emotional intelligence score that adolescent boys have.